Contingent Capital, Tail Risk, and Debt-Induced Collapse - Chen, Nan; Glasserman, Paul; Nouri, Behzad; Pelger, Markus (Review of Financial Studies, 2017)
We study the design and incentive effects of contingent convertible debt. With contingent convertibles, the endogenous bankruptcy boundary can be at either of two levels: one with lower default risk or one at which default precedes conversion. An increase in debt moves the firm from the first regime to the second, a phenomenon we call debt-induced collapse. Setting the conversion trigger sufficiently high avoids this hazard. Given this condition, we investigate the effect of contingent capital and debt maturity on optimal capital structure, debt overhang, and asset substitution. We calibrate the model to large banks during the financial crisis. Received April 10, 2015; editorial decision March 20, 2017 by Editor Leonid Kogan.